USE OF PASTA FROM SEEDS OF CARUM CARVIL IN BAKERY - D. A. Kokh; Z. A. Kokh (Современная наука и инновации)
Caraway seed paste was used as an additive in the amount of 5%, 10%, 15% and 20% when baking wheat bread of the 1st grade. The addition of caraway seedlings to the bread recipe in an amount of 5 to 20% increased the acidity depending on the fermentation time of the dough, this led to a reduction in the technological process due to the biochemical composition of the paste. Using a paste of seedlings from caraway seeds as an additive led to minor changes in the color of the bread. As the amount ofpaste from caraway seedlings increased from 5% to 20%, the sweetness of bread decreased, while stickiness and astringency increased. The quality characteristics of wheat bread grade 1 improved significantly with the addition of 10% paste. Pasta from caraway seedlings was characterized by a water content of 12.1%, which caused significant changes in the water absorption capacity of wheat bread samples. The volume of bread decreased, and the porosity of the bread gradually increased with an increase in the proportion ofpasta from caraway seedlings from 5% to 20%. A significantly lower volume of bread was observed at a concentration of paste from seedlings of caraway seeds of 5%, while for bread enriched with 20% of paste, a higher porosity was characteristic. The results showed that biologically acidified bread was characterized by increased quality, including taste, texture and shelf life.